Regional concentrations of heavy metals in surface soils and risk of body pain in elderly residential population: a national cohort study in China - Bingjie Qu; Bifeng Hu; Rong Rong; Longfei Wu; Xiang Shi; Zheng Feei Ma; Linxi Yuan; Royston Goodacre; Kelvin P. Jordan; Ying Chen (BMC Public Health)
Abstract Background The accumulation of heavy metals in surface soil raises significant environmental and public health concerns around the world. This study aimed to examine the relationship between exposure to heavy metals in surface soil and the risk of pain among residents. Methods Using national data on eight heavy metals (arsenic, cadmium, chromium, copper, lead, mercury, nickel and zinc) in China's surface soil and a population cohort from 2011 to 2018, we analyzed pain occurrences in various body locations. Logistic regression models were used to assess the association between exposure to heavy metal in soil and pain, as adjusting for gender, age, education level, body mass index, living region, and lifestyle. The study included 13,178 individuals. Results Higher exposure to soil arsenic was found to be associated with increased risk of shoulders [adjusted odds ratio (99.99% CI), 1.49 (1.01, 2.19)], wrists [1.68 (1.06, 2.64)] and ankles pain [1.58 (1.01, 2.50)]. No association was found between the remaining seven heavy metals and different types of body pain. Conclusion Our results indicate that higher soil arsenic exposure is associated with an increased risk of pain in specific body regions. This study is the first examining the associations between multiple heavy metals in surface soil and the risks of pain in different body sites. Our findings provide new insights into the health risks of soil heavy metal exposure.